Sociodemographic and clinical follow-up profile of transgender people accessing pre-exposure prophylaxis for the risk of HIV transmission in São Paulo, Brazil (2018-2021) - Marcos Morais Santos Silva; Denize Lotufo Estevam; Mateus Ettori Cardoso; Lucia Yasuko Izumi Nichiata (Epidemiologia e Serviços de Saúde)
ABSTRACT Objective To describe the sociodemographic and clinical follow-up profile of the use of pre-exposure prophylaxis (PrEP) of HIV among transgender people receiving care at a reference health service for sexually transmitted infections and HIV/AIDS in São Paulo, the capital city of São Paulo state, between 2018 and 2021. Method This was a descriptive study with an analysis of sociodemographic data, reasons for seeking PrEP , discontinuation of use and experiences of clinical follow-up. Descriptive statistics were used. Results Among the 53 individuals, the majority were mixed-race (n= 25), transgender women (n= 48), heterosexual (n= 38) and had more than 11 years of study (n= 22). There was a decrease in follow-up visits (n= 14 to n= 3) after the second medical consultation. Conclusion It is necessary to develop strategies to increase PrEP dispensing and continuation among transgender people, especially among Black people and those with lower level of education.